Enhancement of Human Immunodeficiency Virus Type 1 Infection by the CC-Chemokine RANTES Is Independent of the Mechanism of Virus-Cell Fusion - Gordon, Cynthia J. (American Society for Microbiology, 1999)
We have studied the effects of CC-chemokines on human immunodeficiency virus type 1 (HIV-1) infection, focusing on the infectivity enhancement caused by RANTES. High RANTES concentrations increase the infectivity of HIV-1 isolates that use CXC-chemokine receptor 4 for entry. However, RANTES can have a similar enhancing effect on macrophagetropic viruses that enter via CC-chemokine receptor 5 (CCR5), despite binding to the same receptor as the virus. Furthermore, RANTES enhances the infectivity of HIV-1 pseudotyped with the envelope glycoprotein of murine leukemia virus or vesicular stomatitis virus, showing that the mechanism of enhancement is independent of the route of virus-cell fusion. The enhancing effects of RANTES are not mediated via CCR5 or other known chemokine receptors and are not mimicked by MIP-1α or MIP-1β. The N-terminally modified derivative aminooxypentane RANTES (AOP-RANTES) efficiently inhibits HIV-1 infection via CCR5 but otherwise mimics RANTES by enhancing viral infectivity. There are two mechanisms of enhancement: one apparent when target cells are pretreated with RANTES (or AOP-RANTES) for several hours, and the other apparent when RANTES (or AOP-RANTES) is added during virus-cell absorption. We believe that the first mechanism is related to cellular activation by RANTES, whereas the second is an increase in virion attachment to target cells.